2013
DOI: 10.1097/mao.0b013e318288646a
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Pure Tone Hearing Thresholds in an Aging European Population

Abstract: Our results indicate that there is a substantial shared familial effect in ARHI. We found that familial aggregation of ARHI is markedly higher in the low frequencies and that there is a trend toward higher familial aggregation in female compared with male subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…ARHL is a multifactorial disease governed by both genetic and environmental factors (noise, ototoxic drugs), and modulated by the interaction between them (Bowl & Dawson, 2019). Heritability estimates for ARHL lie between 35% and 70% (Christensen, Frederiksen, Frederiksen, & Hoffman, 2001;Gates, Couropmitree, Couropmitree, & Myers, 1999;Hendrickx et al, 2013;Raynor et al, 2009) and noise exposure is a major environmental component that is difficult to separate from the underlying genetic basis (Liberman, 2017;Van Eyken, Van Camp, & Van Laer, 2007). Studies in aged animals and human temporal bones have given great insight into the histological deficit with degenerative changes in the sensory hair cells, the spiral ganglion neurons, and the stria vascularis predominantly described; Figure 1 (Keithley, 2019;Ohlemiller, 2004;Schuknecht, 1964;Schuknecht & Gacek, 1993).…”
mentioning
confidence: 99%
“…ARHL is a multifactorial disease governed by both genetic and environmental factors (noise, ototoxic drugs), and modulated by the interaction between them (Bowl & Dawson, 2019). Heritability estimates for ARHL lie between 35% and 70% (Christensen, Frederiksen, Frederiksen, & Hoffman, 2001;Gates, Couropmitree, Couropmitree, & Myers, 1999;Hendrickx et al, 2013;Raynor et al, 2009) and noise exposure is a major environmental component that is difficult to separate from the underlying genetic basis (Liberman, 2017;Van Eyken, Van Camp, & Van Laer, 2007). Studies in aged animals and human temporal bones have given great insight into the histological deficit with degenerative changes in the sensory hair cells, the spiral ganglion neurons, and the stria vascularis predominantly described; Figure 1 (Keithley, 2019;Ohlemiller, 2004;Schuknecht, 1964;Schuknecht & Gacek, 1993).…”
mentioning
confidence: 99%
“…Environmental factors are thought to account for about half the phenotypic variance of presbycusis (10). Heritability indices of 0.35 to 0.70 have been reported in studies based on hearing thresholds in twins (14), families (15,16), or individuals with self-reported hearing impairment (17).…”
mentioning
confidence: 99%
“…Heritability estimates for age-related hearing loss range as high as 36 and 70% [7][8][9][10][11] suggesting that genetics, along with environmental factors, play a significant role in determining an individual's risk for developing hearing loss. Genome-wide association studies (GWAS) of hearing loss in adults have identified 58 loci associated with the trait in Europeans [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%